The Tamaricetea arceuthoidis: a new class for the continental riparian thickets of the Middle East, Central Asia and the subarid regions of the Lower Volga valley - Akhani, Hossein; Mucina, Ladislav (Lazaroa, 2015)
The new class, the Tamaricetea arceuthoidis, is described covering riparian and intermittent shrubby vegetation of the Irano-Turanian Region in the southwestern and Central Asia and the Lower Volga valley. The dominating species are species of the genus Tamarix that refer high water table in arid and semi-arid habitats with high to moderate salinity. This new class is an ecological analogon of the Nerio-Tamaricetea occurring in the Mediterranean Basin.